An fMRI Study of the Impact of Block Building and Board Games on Spatial Ability - Newman, Sharlene D.; Hansen, Mitchell T.; Gutierrez, Arianna (Frontiers in Psychology, 2016)
Previous studies have found that block play, board games and puzzles result in better spatial ability. This study focused on examining the differential impact of structured block play and board games on spatial processing. Two groups of eight year olds were studied. One group participated in a five session block play training paradigm and the second group had a similar training protocol but played a word/spelling board game. A mental rotation task was assessed before and after training. The mental rotation task was performed during fMRI to observe the neural changes associated with the two play protocols. Only the block play group showed effects of training for both behavioral measures and fMRI measured brain activation. Behaviorally, the block play group showed improvements in both reaction time and accuracy. Additionally, the block play group showed increased involvement of regions that have been linked to spatial working memory and spatial processing after training. The board game group showed non-significant improvements in mental rotation performance, likely related to practice effects, and no training related brain activation differences. While the current study is preliminary, it does suggest that different “spatial” play activities have differential impacts on spatial processing with structured block play but not board games showing a significant impact on mental rotation performance.